2010
DOI: 10.1016/j.jda.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Optimal on-line colorings for minimizing the number of ADMs in optical networks

Abstract: We consider the problem of minimizing the number of ADMs in optical networks. All previous theoretical studies of this problem dealt with the off-line case, where all the lightpaths are given in advance. In a real-life situation, the requests (lightpaths) arrive at the network on-line, and we have to assign them wavelengths so as to minimize the switching cost. This study is thus of great importance in the theory of optical networks. We present a deterministic on-line algorithm for the problem, and show its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…◃ h is the heaviest color 12: end if 13: else 14: if c(v i ) = h then 15: leave v i unmatched 16: 18: choose an arbitrary unmatched vertex v j ∈ U 19:…”
Section: Algorithm 1 Alg(algbalanced)mentioning
confidence: 99%
See 1 more Smart Citation
“…◃ h is the heaviest color 12: end if 13: else 14: if c(v i ) = h then 15: leave v i unmatched 16: 18: choose an arbitrary unmatched vertex v j ∈ U 19:…”
Section: Algorithm 1 Alg(algbalanced)mentioning
confidence: 99%
“…A 7 4 -competitive on-line algorithm for any network topology was presented in [16]. It is shown that this is the best possible competitive ratio for a deterministic on-line algorithm even for ring topologies.…”
Section: Minimization Of Switching Costmentioning
confidence: 99%